Reflections : on the magic of writing - Jones, Diana Wynne (Greenwillow Books, 2012)
This collection of more than twenty-five critical essays, speeches and biographical pieces written and/or chosen by Diana Wynne Jones will be required reading for the author's many fans and for students and teachers of the genre. Reflections includes insightful literary criticism alongside autobiographical anecdotes about reading tours (including an account of the author's famous travel jinx), revelations about the origins of the author's books and thoughts in general about the life of an author and the value of writing. The longest autobiographical piece, "Something About the Author," details Diana's extraordinary childhood and is illustrated with family photographs. Reflections is essential reading for anyone interested in Diana Wynne Jones's work, fantasy or creative writing. With a foreword by Neil Gaiman, introduction and interview by Charlie Butler, bibliography and index.